Stakeholders' roles and responsibilities regarding quality of care. Issue 8 (10th October 2016) - Huotari, Päivi; Havrdová, Zuzana
Abstract : Purpose: The purpose of this paper is to describe how different stakeholders (society, managers, employees and clients) can together ensure the quality of care. Design/methodology/approach: Qualitative data were collected from four focus group interviews conducted in three countries. All interviewees were pursuing a master's degree in social and/or health care management and had begun working in their field after completing their bachelor's degree. The data were analysed using inductive content analysis. Findings: The society and managers are responsible for the care system as a whole and must apply system-oriented, rather than sector-oriented, thinking. Employees are responsible for ensuring the continuity of client services in their work, and managers and employees share the responsibility of achieving the organisational goals and quality standards. The clients are responsible for acting as responsible service users and providing the required information to obtain care. Communication was strongly emphasised in the data, and it necessitates cross-professional and organisational boundaries, professional and political boundaries, as well as boundaries between the professional and the client. Research limitations/implications: Since the interviewees were all pursuing a master's degree in social and/or health care management, when reflecting on their work experience, they may have also been reflecting what they had learned in university. Practical implications: This study emphasises the importance of collaboration and communication between stakeholders in ensuring the quality of care. Unpredictable economies, the ageing population and the ongoing integration and reorganisation of health and social care services in Europe highlight systematic and strategic approach in quality of care. Originality/value: This paper claims that communication between different care stakeholders gives a more systematic and coherent framework for the quality of care. Quality of care is a strategic choice and part of the strategic decision making at the societal, political, organisational and managerial levels.